1987
DOI: 10.1177/108056998705000408
|View full text |Cite
|
Sign up to set email alerts
|

Communication Needs of Recent Graduates

Abstract: The age of the technological office is here. Are we as educators meeting the needs of recent graduates who are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the professional writing community, for example, scholars have surveyed students, alumni, teachers, professionals, and managers about their perceptions of professional writing coursework (Coon & Scanlon, 1997;Cox, 1976). Others have used surveys to identify and assess the kinds of job skills needed by professional writers (Bednar & Olney, 1987;Halpern, 1981;Sapp & Zhang, 2009;Whiteside, 2003), and still others have used surveys to gather data about current workplace practices (Brumberger, 2007;Dawley & Anthony, 2003;Dayton & Hopper, 2010;Moss, 1995). In the composition community, survey research has been used to discover trends in topics such as program assessment (Stitt-Bergh & Hilgers, 2009;Weiser, 1999), satisfaction with university writing centers (Thompson et al, 2009), and instructor perception of multimodal writing (D. Anderson et al, 2006).…”
Section: Survey Research and Methodology In Writing Studiesmentioning
confidence: 99%
“…In the professional writing community, for example, scholars have surveyed students, alumni, teachers, professionals, and managers about their perceptions of professional writing coursework (Coon & Scanlon, 1997;Cox, 1976). Others have used surveys to identify and assess the kinds of job skills needed by professional writers (Bednar & Olney, 1987;Halpern, 1981;Sapp & Zhang, 2009;Whiteside, 2003), and still others have used surveys to gather data about current workplace practices (Brumberger, 2007;Dawley & Anthony, 2003;Dayton & Hopper, 2010;Moss, 1995). In the composition community, survey research has been used to discover trends in topics such as program assessment (Stitt-Bergh & Hilgers, 2009;Weiser, 1999), satisfaction with university writing centers (Thompson et al, 2009), and instructor perception of multimodal writing (D. Anderson et al, 2006).…”
Section: Survey Research and Methodology In Writing Studiesmentioning
confidence: 99%
“…Traditionally, higher education has made limited effort to discover what practitioners believe students should know or be able to do when they leave college. Bednar and Olney's (1987) study discovered that oral communication skills are mandatory 64% of the time in today's organizations. They recommended that educators continually update the business communication curriculum to focus on these skills (Willmington, 1989).…”
Section: Need For Oral Communication Skillsmentioning
confidence: 98%
“…Much of the research on business writing has sought executives' opinions regarding importance and quality of the writing in their firms (Casady & Wasson, 1994;Bednar & Olney, 1987;Bennett & Olney, 1986;Sharplin, Sharplin, & Birdsong, 1986;Storms, 1983;Stine & Skarzenski, 1979). Lack of clarity and conciseness, poor organization, unclear purpose statement, and weak mechanics (grammar, spelling, and punctuation) are reported by researchers as the most frequent writing problems (Epstein, 1999;Bennett & Olney, 1986;Storms, 1983).…”
Section: Purpose and Justification For The Studymentioning
confidence: 99%
“…Most alarming, according to Chase, is that many contemporary business students believe they can be successful without having to write well. A number of research studies, however, have revealed that recent graduates as well as their employers recognize inadequate writing skills as a serious problem and a handicap to both individual advancement and corporate efficiency (Gearhart, 1992; Bednar & Olney, 1987;Storms, 1983;Hewing, 1980). In an attempt to better prepare business students to become effective writers, researchers have focused on revealing the specific weak-nesses inherent in that writing (Waner, 1995), in addition to determining the types of writing required in businesses.…”
mentioning
confidence: 99%